Ailing bones and failing kidneys: a case of chronic cadmium toxicity. (September 2013) - Chakraborty, Sutirtha; Dutta, Arup R; Sural, Saubhik; Gupta, Debkishore; Sen, Susruta
Heavy metal toxicity is often caused by occupational exposure. Chronic cadmium toxicity is a significant health concern among workers engaged in zinc smelting, battery production and silver jewellery industries, particularly in developing countries. We report the case of a 48-year-old man who presented with severe osteoporosis, impaired renal function and acquired Fanconi syndrome. He was finally diagnosed with chronic cadmium toxicity resulting from long-term occupational exposure. Cadmium has a long biological half-life and there is no effective treatment for people who are exposed to it. Therefore, an early diagnosis and prevention of further exposure are important.